Designing Reading Materials for Teaching Agro-Technology Department Based on Communicative Language Teaching in Universitas Islam Madura - Zainollah; Firdausiyah; Jaftiyatur Rohaniyah (Kariman: Jurnal Pendidikan Keislaman, 2023)
The basic goal of teaching and learning English at Agro-Technology Department is to develop the English skills of the students in order that they can understand and comprehend any English references such as textbooks, journals and other sources and they are able to communicate actively. The learning and teaching of English at Agro-Technology Department is considered unable to achieve its objectives. The main problem in this case is there is no an appropriate reading material for the students. The existing material is not in accordance with the needs and the background of the students. Concerning the problem above, a set of suitable instructional material for the students of Agro-Technology Department needs to be developed. The procedure being done in this study are doing need analysis, developing reading materials, expert validation, revising the materials, trying out the materials, and final product. The data from the result of the needs analysis shows most of the students agree to develop reading materials which are suitable with their major content subject namely Agro-Technology science, to include list of vocabulary in the reading materials they are learning, to include grammar review in the future reading materials, to clarify the content of the materials in the explanation, and to arrange the materials according to the degree of its difficulty